Legal Education: Current Issues and Challenges - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2015)
Legal education has had a short history in Singapore. The first law school in what is today known as the Naional University of Singapore (NUS) had its first cohort of graduates in 1961. NUS maintained a monopoly in local legal education for half a century until the second law school was set up in the Singapore Management University (SMU) in 2007. At the time of writing this chapter, a third law school is in the works, to be established in SIM University (UniSIM), with a view to "developing specialist expertise in family and criminal law" and a focus on "multi-disciplinary and applied learning.